The Effect of Health Counseling on Handwashing Technique in Primary Schools - Ane Marantika; Luluk Khusnul Dwihestie (GLOBAL HEALTH SCIENCE GROUP, 2020)
Hand hygiene must be considered because 98% of the spread of germs comes from hands. One easy way to sanitize your hands from spreading germs is through the habit of washing hands properly. Primary School (PS) students aged 6-12 years, where the school is a place for students to gain main experiences. Health services and counseling for primary school age students aim to make every child has the awareness to have a clean and healthy lifestyle. The purpose of this research is to determine the effect of health education on hand washing techniques in primary school students. This type of research is pre-experiment with a one group pretest-posttest design. The study population was all students in grade IV and V State Primary School Gombang, Mlati, Sleman, Yogyakarta, with total sampling technique obtained 42 respondents. Test data analysis using the Wilcoxon test results obtained p-value 0.001, which means that there is an effect of health education on hand washing techniques in students of State Primary School Gombang Mlati Sleman, Yogyakarta. It is hoped that primary students can apply the habit of washing hands properly, namely washing hands in 6 steps with soap and running water in their daily activities.